IMPLEMENTASI KENDALI PID PENALAAN ZIEGLER-NICHOLS MENGGUNAKAN MIKROKONTROLER - Zaidir Jamal (IIB Darmajaya, 2015)
PID control has been widely used in industry as well as been implemented in the control of the liquid level . The research objective is to design PID controller base on microcontroller and then apply it on the miniature hopper-conveyor plant to maintain solid levels of raw materials to remain constant . The dimension of hopper is 25 cm long, 20 cm wide and 25 cm high. The design of PID control uses a separate action based on microcontroller and for the tuning uses open-loop Ziegler-Nichols. The design is implemented in miniature hopper-conveyor plant to move the raw material form of green beans to the hopper using a screw conveyor. The screw conveyor is rotated by a three phase induction motor with inverter speed drive. Level in the hopper is measured by using an ultrasonic sensor module build-in the data acquisition program . The experimental results of implementation on the miniature hopper-conveyor plant shows that PID control provides good performance such as overshoot occurs in 1 cm, or 0.05 % of set point and risetime shows 280 seconds. Key words: PID controller, microcontroller, Ziegler-Nichols, Hopper-conveyor plant